Acod1-mediated inhibition of aerobic glycolysis suppresses osteoclast differentiation and attenuates bone erosion in arthritis - Kachler, Katerina; Andreev, Darja; Thapa, Shreeya; Royzman, Dmytro; Gießl, Andreas; Karuppusamy, Shobika; Llerins Perez, Mireia; Liu, Mengdan; Hofmann, Jörg; Geßner, Arne; Meng, Xianyi; Rauber, Simon; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives: Metabolic changes are crucially involved in osteoclast development and may contribute to bone degradation in rheumatoid arthritis (RA). The enzyme aconitate decarboxylase 1 (Acod1) is known to link the cellular function of monocyte-derived macrophages to their metabolic status. As osteoclasts derive from the monocyte lineage, we hypothesised a role for Acod1 and its metabolite itaconate in osteoclast differentiation and arthritis-associated bone loss. Methods: Itaconate levels were measured in human peripheral blood mononuclear cells (PBMCs) of patients with RA and healthy controls by mass spectrometry. Human and murine osteoclasts were treated with the itaconate derivative 4-octyl-itaconate (4-OI) in vitro. We examined the impact of Acod1-deficiency and 4-OI treatment on bone erosion in mice using K/BxN serum-induced arthritis and human TNF transgenic (hTNFtg) mice. SCENITH and extracellular flux analyses were used to evaluate the metabolic activity of osteoclasts and osteoclast progenitors. Acod1-dependent and itaconate-dependent changes in the osteoclast transcriptome were identified by RNA sequencing. CRISPR/Cas9 gene editing was used to investigate the role of hypoxia-inducible factor (Hif)-1α in Acod1-mediated regulation of osteoclast development. Results: Itaconate levels in PBMCs from patients with RA were inversely correlated with disease activity. Acod1-deficient mice exhibited increased osteoclast numbers and bone erosion in experimental arthritis while 4-OI treatment alleviated inflammatory bone loss in vivo and inhibited human and murine osteoclast differentiation in vitro. Mechanistically, Acod1 suppressed osteoclast differentiation by inhibiting succinate dehydrogenase-dependent production of reactive oxygen species and Hif1α-mediated induction of aerobic glycolysis. Conclusion: Acod1 and itaconate are crucial regulators of osteoclast differentiation and bone loss in inflammatory arthritis.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Arthritis; Experimental; Arthritis; Rheumatoid; Bone Density; Inflammation; Osteoporosis

Eosinophils preserve bone homeostasis by inhibiting excessive osteoclast formation and activity via eosinophil peroxidase. - Andreev, Darja; Kachler, Katerina; Liu, Mengdan; Chen, Zhu; Krishnacoumar, Brenda; Ringer, Mark; Frey, Silke; Krönke, Gerhard; Vöhringer, David; Schett, Georg; Bozec, Aline (Nature Communications, 2024)
Eosinophils are involved in tissue homeostasis. Herein, we unveiled eosinophils as important regulators of bone homeostasis. Eosinophils are localized in proximity to bone-resorbing osteoclasts in the bone marrow. The absence of eosinophils in ΔdblGATA mice results in lower bone mass under steady-state conditions and amplified bone loss upon sex hormone deprivation and inflammatory arthritis. Conversely, increased numbers of eosinophils in IL-5 transgenic mice enhance bone mass under steady-state conditions and protect from hormone- and inflammation- mediated bone loss. Eosinophils strongly inhibit the differentiation and demineralization activity of osteoclasts and lead to profound changes in the transcriptional profile of osteoclasts. This osteoclast-suppressive effect of eosinophils is based on the release of eosinophil peroxidase causing impaired reactive oxygen species and mitogen-activated protein kinase induction in osteoclast precursors. In humans, the number and the activity of eosinophils correlates with bone mass in healthy participants and rheumatoid arthritis patients. Taken together, experimental and human data indicate a regulatory function of eosinophils on bone.
EVALuna2:554518

Osteocyte necrosis triggers osteoclast-mediated bone loss through macrophage-inducible C-type lectin - Andreev, Darja; Liu, Mengdan; Weidner, Daniela; Kachler, Katerina; Faas, Maria; Grüneboom, Anika; Schlötzer-Schrehardt, Ursula; Munoz, Luis Enrique; Steffen, Ulrike; Grötsch, Bettina; Killy, Barbara; Krönke, Gerhard; et al. (Journal of Clinical Investigation, 2020)
Although the control of bone-resorbing osteoclasts through osteocyte-derived RANKL is well defined, little is known about the regulation of osteoclasts by osteocyte death. Indeed, several skeletal diseases, such as bone fracture, osteonecrosis, and inflammation are characterized by excessive osteocyte death. Herein we show that osteoclasts sense damageassociated molecular patterns (DAMPs) released by necrotic osteocytes via macrophage-inducible C-type lectin (Mincle), which induced their differentiation and triggered bone loss. Osteoclasts showed robust Mincle expression upon exposure to necrotic osteocytes in vitro and in vivo. RNA sequencing and metabolic analyses demonstrated that Mincle activation triggers osteoclastogenesis via ITAM-based calcium signaling pathways, skewing osteoclast metabolism toward oxidative phosphorylation. Deletion of Mincle in vivo effectively blocked the activation of osteoclasts after induction of osteocyte death, improved fracture repair, and attenuated inflammation-mediated bone loss. Furthermore, in patients with osteonecrosis, Mincle was highly expressed at skeletal sites of osteocyte death and correlated with strong osteoclastic activity. Taken together, these data point to what we believe is a novel DAMP-mediated process that allows osteoclast activation and bone loss in the context of osteocyte death.
CRIS-Team Scopus Importer:2020-10-16

Regulatory eosinophils induce the resolution of experimental arthritis and appear in remission state of human rheumatoid arthritis - Andreev, Darja; Liu, Mengdan; Kachler, Katerina; Llerins Perez, Mireia; Kirchner, Philipp; Kölle, Julia; Gießl, Andreas; Rauber, Simon; Song, Rui; Aust, Oliver; Grüneboom, Anika; Kleyer, Arnd; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives: Eosinophils possess pro-inflammatory functions in asthma. However, our recent studies have suggested that innate lymphoid cells type 2 (ILC2s) and eosinophils have proresolving properties in rheumatoid arthritis (RA). Nothing is known yet about the mechanisms determining the double-edged role of eosinophils. Therefore, we investigated whether asthma, a paradigm eosinophilic disease, can elicit resolution of chronic arthritis. Methods: Ovalbumin-triggered eosinophilic asthma was combined with K/BxN serum-induced arthritis, where lung and synovial eosinophil subsets were compared by single-cell RNA sequencing (scRNA-seq). To investigate the involvement of the ILC2-interleukin-5 (IL-5) axis, hydrodynamic injection (HDI) of IL-25 and IL-33 plasmids, IL-5 reporter mice and anti-IL-5 antibody treatment were used. In patients with RA, the presence of distinct eosinophil subsets was examined in peripheral blood and synovial tissue. Disease activity of patients with RA with concomitant asthma was monitored before and after mepolizumab (anti-IL-5 antibody) therapy. Results: The induction of eosinophilic asthma caused resolution of murine arthritis and joint tissue protection. ScRNA-seq revealed a specific subset of regulatory eosinophils (rEos) in the joints, distinct from inflammatory eosinophils in the lungs. Mechanistically, synovial rEos expanded on systemic upregulation of IL-5 released by lung ILC2s. Eosinophil depletion abolished the beneficial effect of asthma on arthritis. rEos were consistently present in the synovium of patients with RA in remission, but not in active stage. Remarkably, in patients with RA with concomitant asthma, mepolizumab treatment induced relapse of arthritis. Conclusion: These findings point to a hitherto undiscovered proresolving signature in an eosinophil subset that stimulates arthritis resolution.
CRIS-Team Scopus Importer:2020-11-20
Keywords: arthritis; autoimmune diseases; cytokines; immune system diseases; inflammation; rheumatoid